COMPARISON OF THE OUTCOMES OF ENHANCED RECOVERY AFTER SURGERY (ERAS) VS CONVENTIONAL CARE IN ELECTIVE COLORECTAL SURGERY - Iqbal, Muhammad Tariq; Jatt, Atta Ullah; Arbi, Fawad Mueen (Journal of Ayub Medical College Abbottabad, 2024)
Background: Uncontrolled cell development in the colon, rectum, or appendix is the cause of colorectal cancer, sometimes referred to as colon cancer, rectal cancer, or bowel cancer. Its incidence is higher in developed countries than in developing ones. About 75-95% of cases occur in individuals without significant genetic risk. The aim of Enhanced Recovery After Surgery (ERAS) or fast-track surgery involves the use of several perioperative strategies to facilitate better surgical conditions to achieve faster recovery of the patients which has shown better outcomes in different surgery types. This study aims to compare the outcome of ERAS vs conventional care in elective colorectal surgery. Methods: In this randomized controlled trial, 60 patients undergoing elective colorectal surgery were assessed by dividing them into two groups. Group A patients followed ERAS protocols, while Group B patients followed conventional care techniques. Time for bowel sounds and first flatus were noted. Mean hospital stay was recorded for each patient from operation to discharge. Patients were followed for 4 weeks for surgical site infection assessment. Results: The mean time to return bowel sounds in Group A was 20.63±2.66 hours while in Group B was 27.0±2.07 hours (p-value =0.0001). The mean time to passage of the first flatus in Group A was 18.67±2.38 hours while in Group B was 25.93±2.88 hours (p-value =0.0001). The mean hospital stay in Group A was 3.37±1.75 days while in Group B was 8.30±1.68 days (p-value =0.0001). Surgical site infection was found in 04 (13.33%) patients in group A while in group B, it was found in 09 (30.0%) patients with a p-value of 0.1172. Conclusion: This study concludes that the outcome of enhanced recovery after surgery (ERAS) is better than conventional care in elective colorectal surgery.